UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI MELALUI METODE SQ3R MURID KELAS 5 SD N 26 PAMPANGAN LUBUK BEGALUNG KOTA PADANG - Adriani; Rizal Safaruddin; Zulfamanna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning outcomes of Islamic Religious Education for 5th students at SDN 26 Pampangan Lubuk Begalung, Padang City, through the implementation of the SQ3R method (Survey, Question, Read, Recite, Review). The background of this study is based on the fact that 63.64% of students had not yet achieved the Minimum Mastery Criteria set by the school, which is 80. The learning process was still dominated by the lecture method, causing students to be less active and easily bored. This research employed Classroom Action Research conducted in several cycles involving 22 students as research subjects. Data were collected through observation, learning outcome tests, and documentation. Data analysis was carried out using qualitative and quantitative descriptive techniques. The results show that the implementation of the SQ3R method can increase students’ learning participation and significantly improve their learning outcomes in Islamic Religious Education. Therefore, the SQ3R method is effective as an alternative learning strategy to improve Islamic Religious Education learning outcomes in elementary schools.